Quality of Care in Family Planning Services: Differences Between Formal and Informal Settlements of Kira Municipality, Uganda - Lukyamuzi, Zubair; Tetui, Moses; Fonseca-Rodríguez, Osvaldo; Atuyambe, Lynn; Makumbi, Fredrick Edward; Baroudi, Mazen (Frontiers in Global Women's Health, 2021)
Background: Quality of care (QoC) of family planning (FP) affects contraceptive use, and it varies across types of urban settlement. This study assesses the difference in service delivery point (SDP) structural and process factors between formal and informal urban settlements, and the opinion of the client on the QoC in informal settlements. This is useful in creating an evidence base to advocate for better quality services for the most vulnerable in society. Methods: This was a cross-sectional survey that included SDPs of Kira municipality in Wakiso district, Uganda. Data were collected from all the service points in Kira municipality with the caretakers consented. In addition, using multi-stage sampling, 626 women of reproductive age (15–49 years) who lived in the informal settlements of Kira municipality were interviewed. Data were collected using structured questionnaires, descriptive analysis was carried out in Stata version 14.0, and Chi-square and t-tests were used to compare the informal with the formal settlements. Results: Formal settlements generally had more higher-level SDPs compared to informal settlements (value of p < 0.001). SDPs in the formal settlements provided more FP methods and had more community health workers (CHW) to support their work. Also, SDPs in the formal settlements were more likely to have long-term FP methods available and more likely to have trained personnel to insert and remove implants and IUDs compared to those in informal settlements. Additionally, more SDPs in the formal settlements provided counseling for permanent, long-term, and short-term FP methods. Of the 626 interviewed women, most of the women (68.6%) reported that they would not return to the previous FP provider or refer a friend to the same provider (72.7%). Conclusions: There is a lower quality FP services in the informal settlements with a commensurable effect on the client satisfaction with the services. Therefore, improving the quality of FP services in informal settlements should be a top priority. Improved quality of services could act as a motivation to increase the uptake of modern contraceptives in such settings.